An early medieval dual-currency economy: bullion and coin in the Danelaw - Kershaw, J (Cambridge University Press, 2017)
Metal detecting in England has recovered a large number of Viking Age single finds that have been reported to the Portable Antiquities Scheme. These reveal that silver bullion of Scandinavian origin was used as currency throughout the Danelaw between AD 865 and 940. Standardised weights of copper alloy were an integral part of this metal-weight economy. Bullion was not the sole means of silver payment during this period: coinage had long been used in the occupied Anglo-Saxon territories and continued to be minted under the Vikings. The resulting dual-currency economy may have facilitated trade with neighbouring Scandinavian territories, but the two currencies also served as markers of cultural identity, offering a choice of monetary media.